A children's bedtime book - Warbe; Frederick (London Fredrick Warne, 2000)
Poems, stories and fairy tales including Red Riding Hood, Sleeping Beauty, Snow White, from A Gallery of Children; The Twins and Miss Waterlow in Bed, plus rhymes from A Child's Garden of Verses and Mother Goose Treasury.